2019
DOI: 10.1093/nar/gkz138
|View full text |Cite|
|
Sign up to set email alerts
|

The nuclear structural protein NuMA is a negative regulator of 53BP1 in DNA double-strand break repair

Abstract: P53-binding protein 1 (53BP1) mediates DNA repair pathway choice and promotes checkpoint activation. Chromatin marks induced by DNA double-strand breaks and recognized by 53BP1 enable focal accumulation of this multifunctional repair factor at damaged chromatin. Here, we unveil an additional level of regulation of 53BP1 outside repair foci. 53BP1 movements are constrained throughout the nucleoplasm and increase in response to DNA damage. 53BP1 interacts with the structural protein NuMA, which controls 53BP1 di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…Notably, some of the sites whose phosphorylation was enhanced by DNA‐PKi were found on well‐documented DDR players; e.g., H2AX, NBS1, TOPBP1, KAP‐1, SMC1, and RIF1 (Fig 3D). Further validation of this pattern was carried out in NL‐550 and U2‐OS cells focusing on three ATM targets in this group, pS824/KAP‐1, pS343/NBS1, and pS395/NUMA (Vidi et al , 2014; Salvador Moreno et al , 2019). For this purpose, we used Western blotting analysis based on phospho‐specific antibodies directed against these sites (Figs 3E and EV2).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, some of the sites whose phosphorylation was enhanced by DNA‐PKi were found on well‐documented DDR players; e.g., H2AX, NBS1, TOPBP1, KAP‐1, SMC1, and RIF1 (Fig 3D). Further validation of this pattern was carried out in NL‐550 and U2‐OS cells focusing on three ATM targets in this group, pS824/KAP‐1, pS343/NBS1, and pS395/NUMA (Vidi et al , 2014; Salvador Moreno et al , 2019). For this purpose, we used Western blotting analysis based on phospho‐specific antibodies directed against these sites (Figs 3E and EV2).…”
Section: Resultsmentioning
confidence: 99%
“…NuMA is phosphorylated by a number of different kinases, and it has been shown that NuMA phosphorylation is required for attachment to, and assembly of, the mitotic spindle [ 41 ]. We found an increase in the presence of Ser395 phospho-NuMA, through which it regulates binding of 53BP1 to damaged DNA [ 42 ]. The mobility of 53BP1 within the nucleus is restricted by the binding of phospho-NuMA, which limits the binding of 53BP1 to sites of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear mitotic apparatus protein 1 (Numa1) is one of the most abundant structural components of the interphase nucleus and has been suggested to be a major constituent of the proposed nuclear scaffold termed the nuclear matrix [ 36 ]. Nuclear Numa 1 serves diverse functions, e.g., in chromatin organization [ 37 , 38 ] and DNA repair [ 39 , 40 ]. Interestingly, it has been shown to directly interact with HPV oncoproteins [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that altered expression of global chromatin organizing factors may have various potential implications, but to clarify their role in the treatment sensitivity of OPSCC requires future functional studies. Potentially influencing DNA repair and radiation sensitivity in a direct manner, Numa1 has been described to promote homologous recombination repair [ 40 ] but to inhibit the non-homologous endjoining promoting factor 53BP1 by restricting its diffusion in the nucleoplasm [ 39 ]. RBBP4 on the one hand and SLC3A2 and cortactin on the other have been explicitly described as radiosensitivity or radioresistance factors, respectively [ 58 , 65 , 66 , 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%